Biochemical delineation of oat (Avena sativa) accessions for nutritional improvement - CHAWLA, RUKOO; JATTAN, MINAKSHI; PHOGAT, D S; KUMARI, NISHA; KUMAR, SANDEEP; SHARMA, AMIT; CHAUHAN, DEEKSHA; MANDAL, NEELAM KUMARI (The Indian Journal of Agricultural Sciences, 2023)
Oat (Avena sativa L.) is a unique multifaceted crop used for fodder and grain purpose. It’s grain has tremendous potential to offer health benefits, especially with the heightened emphasis on nutrition and food security. With this aim, quality traits were investigated among 62 oat genotypes, demonstrating significant variation. The biochemical analysis was conducted in laboratory of department of Genetics and Plant Breeding of CCS Haryana Agricultural University, Hisar during 2019–21. Quality parameters depicted a wide range for seed crude protein (8.16–19.18%), forage crude protein (5.17–11.42%), phenol (0.61–1.22%), beta-glucan content (0.32–7.55%), total soluble sugar (4.90–8.49%), reducing sugar (1.07–4.28%) and non-reducing sugar (2.02–6.38%). The current research covered wide and powerful analytical approaches that helped to underpin the selection of the most promising genotypes and evaluated the contribution of different traits to heterogeneity. Furthermore, non-reducing sugar, reducing sugar and seed crude protein were emerged to be the major contributors of PC1, PC2 and PC3, respectively. The genotypes GP 492, HFO 1107, HFO 1003, HFO 1016, OS 403, HFO1105 and HFO 806 were the best performing based on quality parameters. Promiscuous genotypes can serve as pioneers in oat improvement programs, enabling the enhancement of nutritional value. These insights expand the prospects for the food industry and hence appraise the significance of oats among other cereals.